Measures of Adiposity and Risk of Testing Positive for SARS-CoV-2 in the UK Biobank Study - Rebecca A. G. Christensen; Shelby L. Sturrock; Jasleen Arneja; Jennifer D. Brooks (Journal of Obesity)
Objective. To assess if body mass index (BMI) and high waist circumference (HWC) are associated with testing positive for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods. 9,386 UK Biobank study participants tested for SARS-CoV-2 from March 16th 2020 to June 29th 2020 were analyzed. A forward model building approach was used to estimate adjusted risk ratios (RR) and 95% confidence intervals (95% CI). Analyses were stratified by age due to a significant first-order interaction between age and HWC. Results. Approximately 17% (n = 1,577) of participants tested positive for SARS-CoV-2. BMI category had a linear association with testing positive for SARS-CoV-2 among participants <65 years (RR = 1.09, 95% CI 1.02–1.17). For participants ≥65 years, only obesity class II (RR = 1.38, 95% CI 1.10–1.74) had a significantly greater risk of testing positive for SARS-CoV-2 than those who were underweight/normal weight. While HWC was not associated with testing positive for SARS-CoV-2 in those <65 years, having an HWC was associated with an increased risk of testing positive for SARS-CoV-2 in participants ≥65 years (RR = 1.12, 95% CI 1.00–1.27). Conclusion. The associations of BMI and HWC with testing positive for SARS-CoV-2 differed by age. Notably, HWC was associated with testing positive in those ≥65 years, but not those who were younger, independent of BMI. This suggests that measures of adiposity in addition to BMI may be used to identify older individuals at greater risk of testing positive for SARS-CoV-2.